Effect of flexor tendon tenotomy of the diabetic hammertoe on plantar pressure: a randomized controlled trial - Peter Rossing; Jesper Bencke; Klaus Kirketerp-Møller; Marie Frimodt-Moller; Jonas Askø Andersen; Anne Rasmussen; Susanne Engberg (BMJ Open Diabetes Research & Care)
Introduction The aim of this study was to evaluate the effects of flexor tendon tenotomy treatment of the diabetic hammertoe deformity on plantar pressure.Research design and methods The study was a substudy including participants from a randomized study on tenotomy treatment of diabetic hammertoes. This study was conducted between December 20, 2019 and June 22, 2021. Participants were randomized to tenotomy and standard non-surgical treatment or standard non-surgical treatment alone. Barefoot plantar pressure measurement was performed pre-intervention and 3 months post-intervention. Primary outcome was change in peak plantar pressure post tenotomy treatment.Results Of the 95 participants screened in the original study, 45 (57.8% male) were included andcompleted this substudy. Of the 45 participants, 22 were randomized to intervention. The average age of participants was 65.6 ((SD±) 9.5) years and 30 (66.7%) had type 2 diabetes.The average peak plantar pressure (PPP) in toe regions of the participants in the intervention group was significantly (p<0.0001) reduced from 205.6 kPa ((Q1–Q3) 152.0–289.1) pre-intervention to 61.3 kPa (39.1–100.5) post-intervention. The average reduction in PPP of toe regions for participants in the intervention group (−145.3 kPa (−225.9 to −56.2)) was significantly (p=0.00017) higher than what was observed for participants in the control group (−1.6 kPa (−30.2 to 27.9)).Conclusion This study found that tenotomies of the diabetic hammertoe reduces plantar pressure affecting the treated toes. This likely explains the positive effects of tenotomy treatment on diabetic foot ulcers.